Method for manufacturing mullite-high silica glass multiphase material by using hard clay
By mixing hard clay, topaz, molybdenum tailings and lithium mica lithium slag and sintering, mullite-high silicone oxygen glass composite material with excellent refraction resistance and low thermal expansion coefficient was prepared, solving the problem of mullite production without hard clay.
Patent Information
- Application Number
- CN202510324444.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-19
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-03-19
AI Technical Summary
How to use small materials such as hard clay to prepare high-quality mullite-high silicone oxygen glass composite materials, solving the problem of mullite produced by hard clay as raw materials in the prior art.
By mixing hard clay, topaz, molybdenum tailings and lithium mica lithium slag, crushing and grading, adding a mixture of sodium dihydrate dihydrate, yttrium oxide and tungsten trioxide for grinding, pressing and molding, and sintering by controlling the heating rate and insulation time, mullite-high silicone oxygen glass composite phase material was prepared.
The prepared mullite-high silicone oxygen glass composite material has excellent refraction resistance and low thermal expansion coefficient and excellent performance.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of refractory material preparation, and specifically relates to a method for manufacturing a mullite-high silica glass composite material by utilizing hard clay. Background Art
[0002] Mullite-high silica glass composite material is a new type of refractory raw material composed of mullite and amorphous high silica glass (glass phase mainly composed of SiO2). This composite material has excellent properties such as high refractoriness, low expansion coefficient, high hardness, and wear resistance. At high temperatures, the high silica glass phase transforms into a high-viscosity liquid phase, which is beneficial to high-temperature performance. At low temperatures, due to the low thermal expansion coefficient of the high silica glass material and the absence of free quartz in the phase composition, mullite forms a cross-network structure, which is beneficial to improving thermal shock resistance.
[0003] Mullite is a high-quality refractory raw material and the most stable binary solid solution in the Al2O3-SiO2 binary system under normal pressure. Natural mullite with the chemical formula of 3Al2O3·2SiO2 is very rare and is usually synthesized artificially by sintering or electric melting. Due to its excellent performance, mullite is widely used in refractory materials, ceramics, metallurgy, casting, electronics and other industries. It has the characteristics of high temperature resistance, high strength, low thermal conductivity, and significant energy saving effect. It is suitable for the lining of petroleum cracking furnaces, metallurgical hot air furnaces, ceramic roller kilns, tunnel kilns, electric porcelain drawer kilns, glass crucible kilns and various electric furnaces.
[0004] With the rapid development of modern industry, the output of steel and non-ferrous metals has continued to grow, and the production of refractory materials has also increased rapidly. The amount of tailings (small materials) discharged from refractory raw material mines is increasing day by day. At the same time, with the increasing depletion of rich ore resources, the proportion of lean ore and tailings resources mining is increasing, and the scale of tailings use is expanding. Therefore, the comprehensive utilization of tailings can not only reduce the storage of tailings, but also improve the environmental sanitation of mining areas.
[0005] At present, there are many types of mullite in my country. According to the synthesis method, it can be divided into sintered mullite and fused mullite. According to the raw materials, it can be divided into coal gangue-based mullite, alumina-based mullite (including all-natural), alumina-based mullite (high purity), etc., but there is no mullite produced with hard clay as raw material. Therefore, how to use small materials such as hard clay to prepare mullite-high silica glass composite materials has become a technical problem that needs to be solved urgently. Summary of the invention
[0006] The purpose of the present invention is to provide a method for manufacturing a mullite-high silica glass composite material using hard clay. The mullite-high silica glass composite material prepared by the method has excellent refractoriness and a low thermal expansion coefficient.
[0007] The method for manufacturing a mullite-high silica glass composite material using hard clay according to the present invention comprises the following steps: (1) Mixing hard clay, topaz, molybdenum tailings and lithium mica slag to obtain a mixture, and then crushing, grading and screening to prepare 5-8 mm mixed granular materials, 3-5 mm mixed granular materials and 2-3 mm mixed granular materials; wherein, in the mixture, by weight, hard clay 71-72.5 parts, topaz 26-28 parts, molybdenum tailings 5-7.5 parts, lithium mica slag 5-7 parts; (2) The 5-8 mm mixed material particles, 3-5 mm mixed material particles and 2-3 mm mixed material particles prepared in step (1) are mixed evenly, and then a mixture of sodium dihydrogen phosphate dihydrate, yttrium oxide and tungsten trioxide is added and ground to prepare a powder; (3) Pressing the powder into green compacts and then drying them; (4) First, the temperature is raised to 1000°C at a rate of 4.5°C / min, then the temperature is raised to 1230-1250°C at a rate of 2.3°C / min, and then the temperature is kept at this temperature. Finally, the temperature is cooled to room temperature in the furnace to prepare a mullite-high silica glass composite material.
[0008] in: The hard clay in step (1) has the following chemical composition, in terms of mass percentage: Al2O3 39.09%, SiO2 44.56%, Fe2O3 1.62%, TiO2 0.89%, CaO 0.28%, MgO 0.24%, and loss on ignition 13.32%.
[0009] The topaz described in step (1) has the following chemical composition, calculated by mass percentage: Al2O3 53.69%, SiO2 34.64%, MgO 0.01%, CaO 0.22%, Fe2O3 0.29%, TiO2 0.06%, K2O 0.03%, Na2O 0.01%, and F1 1.05%.
[0010] The molybdenum tailings described in step (1) have the following chemical composition, calculated by mass percentage: SiO2 75.68%, Al2O3 12.50%, K2O 5.54%, Na2O 2.48%, CaO 0.75%, MgO 0.56%, and loss on ignition 2.49%.
[0011] The lithium mica slag described in step (1) has the following chemical composition, calculated by mass percentage: SiO2 55.79%, Al2O3 21.21%, Fe2O3 0.87%, CaO 3.21%, MgO 0.15%, K2O 4.54%, Na2O 10.59%, TiO2 2.97%, SO3 0.03%, and loss on ignition 0.64%.
[0012] The mass ratio of the 5-8 mm mixed material particles, the 3-5 mm mixed material particles, and the 2-3 mm mixed material particles in step (1) is 22:35:43.
[0013] In step (2), the mixture of sodium dihydrogen phosphate dihydrate, yttrium oxide and tungsten trioxide accounts for 3.5-3.8% of the total mass of the mixed material particles of 5-8 mm, the mixed material particles of 3-5 mm and the mixed material particles of 2-3 mm.
[0014] In step (2), the mass ratio of sodium dihydrogen phosphate dihydrate, yttrium oxide and tungsten trioxide is 1.38:1:1.
[0015] The grinding time in step (2) is 13-15 hours, and after grinding, the mixture is sieved through a 300-mesh sieve to obtain a powder.
[0016] In step (3), the pressing pressure is 80 MPa, the drying temperature is 105-108°C, and the drying time is 24 hours.
[0017] The holding time in step (4) is 3.3-3.5h.
[0018] Compared with the prior art, the present invention has the following beneficial effects: (1) The method of using hard clay to manufacture mullite-high silica glass composite material of the present invention uses hard clay and topaz as main raw materials, and molybdenum tailings and lithium mica slag as auxiliary raw materials, wherein the sintering of topaz at high temperature can generate mullite phase, SiF4 and HF gas, and the presence of SiF4 and HF gas can promote the formation of mullite. In addition to containing a large amount of silicon dioxide and aluminum oxide, molybdenum tailings and lithium mica slag have a high alkali metal content. Their addition can ensure the formation of mullite densification at high temperature, inhibit the transformation of quartz crystal form below high temperature, and convert all excess silicon dioxide into high silica glass phase. The glass phase has high viscosity, so that the prepared composite material has excellent high temperature performance. At low temperature, cristobalite is eliminated, and mullite forms a cross-network structure, so that it has a lower thermal expansion coefficient.
[0019] (2) The method of using hard clay to manufacture mullite-high silica glass composite material of the present invention comprises the following steps: crushing, decomposing and screening a mixture obtained by mixing hard clay, topaz, molybdenum tailings and lithium mica slag, generating lattice defects by mechanical external force to improve the reaction activity, adding a mixture of sodium dihydrogen phosphate dihydrate, yttrium oxide and tungsten trioxide as a sintering promoter to reduce the reaction temperature during firing, pressing and molding to promote the chemical reaction between the materials, and finally sintering by controlling the heating rate and the holding time to obtain a mullite-high silica glass composite material with excellent performance.
[0020] (3) The method of using hard clay to manufacture mullite-high silica glass composite material of the present invention uses a mixture of sodium dihydrogen phosphate dihydrate, yttrium oxide and tungsten trioxide as a sintering agent, and sodium dihydrogen phosphate dihydrate can be used as a glass phase to promote Al 3+ and Si 4+ The diffusion rate at the interface is conducive to the formation of mullite phase; the addition of yttrium oxide can significantly reduce the firing temperature and promote the densification of mullite phase; the addition of tungsten trioxide can promote the nucleation of mullite and the formation of high-silica glass phase at high temperature. The synergistic effect of the three ensures the performance of mullite-high-silica glass composite materials prepared at a lower firing temperature.
[0021] (4) The mullite-high silica glass composite material prepared by the method described in the present invention has excellent refractoriness and a low thermal expansion coefficient. DETAILED DESCRIPTION
[0022] The present invention is further described below with reference to the embodiments.
[0023] Example 1 The method for manufacturing a mullite-high silica glass composite material using hard clay described in Example 1 is composed of the following steps: (1) mixing hard clay, topaz, molybdenum tailings and lepidolite lithium slag to obtain a mixture, and then crushing, grading and screening to prepare 5-8 mm mixed granular materials, 3-5 mm mixed granular materials and 2-3 mm mixed granular materials; wherein the mixture contains 71 parts of hard clay, 28 parts of topaz, 5 parts of molybdenum tailings and 7 parts of lepidolite lithium slag by weight; (2) The 5-8 mm mixed material particles, 3-5 mm mixed material particles and 2-3 mm mixed material particles prepared in step (1) are mixed evenly, and then a mixture of sodium dihydrogen phosphate dihydrate, yttrium oxide and tungsten trioxide is added and ground to prepare a powder; (3) Pressing the powder into green compacts and then drying them; (4) First, the temperature was raised to 1000°C at a rate of 4.5°C / min, then raised to 1240°C at a rate of 2.3°C / min and kept warm, and finally cooled to room temperature in the furnace to obtain a mullite-high silica glass composite material.
[0024] in: The hard clay in step (1) has the following chemical composition, in terms of mass percentage: Al2O3 39.09%, SiO2 44.56%, Fe2O3 1.62%, TiO2 0.89%, CaO 0.28%, MgO 0.24%, and loss on ignition 13.32%.
[0025] The topaz described in step (1) has the following chemical composition, calculated by mass percentage: Al2O3 53.69%, SiO2 34.64%, MgO 0.01%, CaO 0.22%, Fe2O3 0.29%, TiO2 0.06%, K2O 0.03%, Na2O 0.01%, and F1 1.05%.
[0026] The molybdenum tailings described in step (1) have the following chemical composition, calculated by mass percentage: SiO2 75.68%, Al2O3 12.50%, K2O 5.54%, Na2O 2.48%, CaO 0.75%, MgO 0.56%, and loss on ignition 2.49%.
[0027] The lithium mica slag described in step (1) has the following chemical composition, calculated by mass percentage: SiO2 55.79%, Al2O3 21.21%, Fe2O3 0.87%, CaO 3.21%, MgO 0.15%, K2O 4.54%, Na2O 10.59%, TiO2 2.97%, SO3 0.03%, and loss on ignition 0.64%.
[0028] The mass ratio of the 5-8 mm mixed material particles, the 3-5 mm mixed material particles, and the 2-3 mm mixed material particles in step (1) is 22:35:43.
[0029] In step (2), the mixture of sodium dihydrogen phosphate dihydrate, yttrium oxide and tungsten trioxide accounts for 3.6% of the total mass of the mixed material particles of 5-8 mm, the mixed material particles of 3-5 mm and the mixed material particles of 2-3 mm.
[0030] In step (2), the mass ratio of sodium dihydrogen phosphate dihydrate, yttrium oxide and tungsten trioxide is 1.38:1:1.
[0031] The grinding time in step (2) is 14 hours, and after grinding, the mixture is sieved through a 300-mesh sieve to obtain a powder.
[0032] In step (3), the pressing pressure is 80 MPa, the drying temperature is 106° C., and the drying time is 24 h.
[0033] The holding time in step (4) is 3.4 h.
[0034] The performance test of the mullite-high silica glass composite material prepared in Example 1 showed that the volume density was 2.65 g / cm 3 , the refractoriness is 1830℃, and the thermal expansion coefficient at 1300℃ is 3.5*10 -6 / ℃.
[0035] Example 2 The method for manufacturing a mullite-high silica glass composite material using hard clay described in Example 2 is composed of the following steps: (1) mixing hard clay, topaz, molybdenum tailings and lepidolite lithium slag to obtain a mixture, and then crushing, grading and screening to prepare 5-8 mm mixed granular materials, 3-5 mm mixed granular materials and 2-3 mm mixed granular materials; wherein the mixture contains 71.8 parts of hard clay, 27 parts of topaz, 7.5 parts of molybdenum tailings and 6 parts of lepidolite lithium slag by weight; (2) The 5-8 mm mixed material particles, 3-5 mm mixed material particles and 2-3 mm mixed material particles prepared in step (1) are mixed evenly, and then a mixture of sodium dihydrogen phosphate dihydrate, yttrium oxide and tungsten trioxide is added and ground to prepare a powder; (3) Pressing the powder into green compacts and then drying them; (4) First, the temperature was raised to 1000°C at a rate of 4.5°C / min, then raised to 1250°C at a rate of 2.3°C / min and kept warm, and finally cooled to room temperature in the furnace to obtain a mullite-high silica glass composite material.
[0036] in: The hard clay in step (1) has the following chemical composition, in terms of mass percentage: Al2O3 39.09%, SiO2 44.56%, Fe2O3 1.62%, TiO2 0.89%, CaO 0.28%, MgO 0.24%, and loss on ignition 13.32%.
[0037] The topaz described in step (1) has the following chemical composition, calculated by mass percentage: Al2O3 53.69%, SiO2 34.64%, MgO 0.01%, CaO 0.22%, Fe2O3 0.29%, TiO2 0.06%, K2O 0.03%, Na2O 0.01%, and F1 1.05%.
[0038] The molybdenum tailings described in step (1) have the following chemical composition, calculated by mass percentage: SiO2 75.68%, Al2O3 12.50%, K2O 5.54%, Na2O 2.48%, CaO 0.75%, MgO 0.56%, and loss on ignition 2.49%.
[0039] The lithium mica slag described in step (1) has the following chemical composition, calculated by mass percentage: SiO2 55.79%, Al2O3 21.21%, Fe2O3 0.87%, CaO 3.21%, MgO 0.15%, K2O 4.54%, Na2O 10.59%, TiO2 2.97%, SO3 0.03%, and loss on ignition 0.64%.
[0040] The mass ratio of the 5-8 mm mixed material particles, the 3-5 mm mixed material particles, and the 2-3 mm mixed material particles in step (1) is 22:35:43.
[0041] In step (2), the mixture of sodium dihydrogen phosphate dihydrate, yttrium oxide and tungsten trioxide accounts for 3.8% of the total mass of the mixed material particles of 5-8 mm, the mixed material particles of 3-5 mm and the mixed material particles of 2-3 mm.
[0042] In step (2), the mass ratio of sodium dihydrogen phosphate dihydrate, yttrium oxide and tungsten trioxide is 1.38:1:1.
[0043] The grinding time in step (2) is 15 hours, and after grinding, the mixture is sieved through a 300-mesh sieve to obtain a powder.
[0044] In step (3), the pressing pressure is 80 MPa, the drying temperature is 108° C., and the drying time is 24 h.
[0045] The holding time in step (4) is 3.3 h.
[0046] The performance test of the mullite-high silica glass composite material prepared in Example 2 showed that its volume density was 2.64 g / cm 3 , the refractoriness is 1830℃, and the thermal expansion coefficient at 1300℃ is 3.7*10 -6 / ℃.
[0047] Example 3 The method for manufacturing a mullite-high silica glass composite material using hard clay described in Example 3 is composed of the following steps: (1) mixing hard clay, topaz, molybdenum tailings and lepidolite lithium slag to obtain a mixture, and then crushing, grading and screening to prepare 5-8 mm mixed granular materials, 3-5 mm mixed granular materials and 2-3 mm mixed granular materials; wherein the mixture contains 72.5 parts of hard clay, 26 parts of topaz, 6.5 parts of molybdenum tailings and 5 parts of lepidolite lithium slag by weight; (2) The 5-8 mm mixed material particles, 3-5 mm mixed material particles and 2-3 mm mixed material particles prepared in step (1) are mixed evenly, and then a mixture of sodium dihydrogen phosphate dihydrate, yttrium oxide and tungsten trioxide is added and ground to prepare a powder; (3) Pressing the powder into green compacts and then drying them; (4) First, the temperature was raised to 1000°C at a rate of 4.5°C / min, then raised to 1230°C at a rate of 2.3°C / min and kept warm, and finally cooled to room temperature in the furnace to obtain a mullite-high silica glass composite material.
[0048] in: The hard clay in step (1) has the following chemical composition, in terms of mass percentage: Al2O3 39.09%, SiO2 44.56%, Fe2O3 1.62%, TiO2 0.89%, CaO 0.28%, MgO 0.24%, and loss on ignition 13.32%.
[0049] The topaz described in step (1) has the following chemical composition, calculated by mass percentage: Al2O3 53.69%, SiO2 34.64%, MgO 0.01%, CaO 0.22%, Fe2O3 0.29%, TiO2 0.06%, K2O 0.03%, Na2O 0.01%, and F1 1.05%.
[0050] The molybdenum tailings described in step (1) have the following chemical composition, calculated by mass percentage: SiO2 75.68%, Al2O3 12.50%, K2O 5.54%, Na2O 2.48%, CaO 0.75%, MgO 0.56%, and loss on ignition 2.49%.
[0051] The lithium mica slag described in step (1) has the following chemical composition, calculated by mass percentage: SiO2 55.79%, Al2O3 21.21%, Fe2O3 0.87%, CaO 3.21%, MgO 0.15%, K2O 4.54%, Na2O 10.59%, TiO2 2.97%, SO3 0.03%, and loss on ignition 0.64%.
[0052] The mass ratio of the 5-8 mm mixed material particles, the 3-5 mm mixed material particles, and the 2-3 mm mixed material particles in step (1) is 22:35:43.
[0053] In step (2), the mixture of sodium dihydrogen phosphate dihydrate, yttrium oxide and tungsten trioxide accounts for 3.5% of the total mass of the mixed material particles of 5-8 mm, the mixed material particles of 3-5 mm and the mixed material particles of 2-3 mm.
[0054] In step (2), the mass ratio of sodium dihydrogen phosphate dihydrate, yttrium oxide and tungsten trioxide is 1.38:1:1.
[0055] The grinding time in step (2) is 13 hours, and after grinding, the mixture is sieved through a 300-mesh sieve to obtain a powder.
[0056] In step (3), the pressing pressure is 80 MPa, the drying temperature is 105° C., and the drying time is 24 h.
[0057] The holding time in step (4) is 3.5 h.
[0058] The performance test of the mullite-high silica glass composite material prepared in Example 3 showed that its volume density was 2.62 g / cm 3 , the refractoriness is 1820℃, and the thermal expansion coefficient at 1300℃ is 3.7*10 -6 / ℃.
[0059] Comparative Example 1 The method for preparing mullite-high silica glass composite material using hard clay described in this comparative example 1 is the same as that in Example 1, except that the mixture of sodium dihydrogen phosphate dihydrate, yttrium oxide and tungsten trioxide is not added in step (2).
[0060] The performance test of the mullite-high silica glass composite material prepared in Comparative Example 1 showed that its volume density was 2.45 g / cm 3 , the refractoriness is 1600℃, and the thermal expansion coefficient at 1300℃ is 5.6*10 -6 / ℃.
[0061] Comparative Example 2 The method for preparing mullite-high silica glass composite material using hard clay described in this comparative example 2 is the same as that in Example 1, with the only difference being that molybdenum tailings and lithium mica lithium slag are not added in step (1), and the mixture in step (1) is composed of 71 parts of hard clay and 28 parts of topaz by weight.
[0062] The performance test of the mullite-high silica glass composite material prepared in Comparative Example 2 showed that its volume density was 2.52 g / cm 3, the refractoriness is 1670℃, and the thermal expansion coefficient at 1300℃ is 6.8*10 -6 / ℃.
Claims
1. A method for manufacturing a mullite-high silica glass composite material using hard clay, characterized in that: It consists of the following steps: (1) Mixing hard clay, topaz, molybdenum tailings and lithium mica slag to obtain a mixture, and then crushing, grading and screening to prepare 5-8 mm mixed granular materials, 3-5 mm mixed granular materials and 2-3 mm mixed granular materials; wherein, in the mixture, by weight, hard clay 71-72.5 parts, topaz 26-28 parts, molybdenum tailings 5-7.5 parts, lithium mica slag 5-7 parts; (2) The 5-8 mm mixed material particles, 3-5 mm mixed material particles and 2-3 mm mixed material particles prepared in step (1) are mixed evenly, and then a mixture of sodium dihydrogen phosphate dihydrate, yttrium oxide and tungsten trioxide is added and ground to prepare a powder; (3) Pressing the powder into green compacts and then drying them; (4) First, the temperature is raised to 1000°C at a rate of 4.5°C / min, then the temperature is raised to 1230-1250°C at a rate of 2.3°C / min, and then the temperature is kept at this temperature. Finally, the temperature is cooled to room temperature in the furnace to prepare a mullite-high silica glass composite material.
2. The method for manufacturing mullite-high silica glass composite material using hard clay according to claim 1, characterized in that: The hard clay in step (1) has the following chemical composition, in terms of mass percentage: Al2O3 39.09%, SiO2 44.56%, Fe2O3 1.62%, TiO2 0.89%, CaO 0.28%, MgO 0.24%, and loss on ignition 13.32%.
3. The method for manufacturing mullite-high silica glass composite material using hard clay according to claim 1, characterized in that: The topaz described in step (1) has the following chemical composition, calculated by mass percentage: Al2O3 53.69%, SiO2 34.64%, MgO 0.01%, CaO 0.22%, Fe2O3 0.29%, TiO2 0.06%, K2O 0.03%, Na2O 0.01%, and F1 1.05%.
4. The method for manufacturing mullite-high silica glass composite material using hard clay according to claim 1, characterized in that: The molybdenum tailings described in step (1) have the following chemical composition, calculated by mass percentage: SiO2 75.68%, Al2O3 12.50%, K2O 5.54%, Na2O 2.48%, CaO 0.75%, MgO 0.56%, and loss on ignition 2.49%.
5. The method for manufacturing mullite-high silica glass composite material using hard clay according to claim 1, characterized in that: The lithium mica slag described in step (1) has the following chemical composition, calculated by mass percentage: SiO2 55.79%, Al2O3 21.21%, Fe2O3 0.87%, CaO 3.21%, MgO 0.15%, K2O 4.54%, Na2O 10.59%, TiO2 2.97%, SO3 0.03%, and loss on ignition 0.64%.
6. The method for manufacturing mullite-high silica glass composite material using hard clay according to claim 1, characterized in that: The mass ratio of the 5-8 mm mixed material particles, the 3-5 mm mixed material particles, and the 2-3 mm mixed material particles in step (1) is 22:35:
43.
7. The method for manufacturing mullite-high silica glass composite material using hard clay according to claim 1, characterized in that: In step (2), the mixture of sodium dihydrogen phosphate dihydrate, yttrium oxide and tungsten trioxide accounts for 3.5-3.8% of the total mass of the mixed material particles of 5-8 mm, the mixed material particles of 3-5 mm and the mixed material particles of 2-3 mm.
8. The method for manufacturing mullite-high silica glass composite material using hard clay according to claim 1, characterized in that: In step (2), the mass ratio of sodium dihydrogen phosphate dihydrate, yttrium oxide and tungsten trioxide is 1.38:1:
1.
9. The method for manufacturing mullite-high silica glass composite material using hard clay according to claim 1, characterized in that: The grinding time in step (2) is 13-15 hours, and after grinding, the mixture is sieved through a 300-mesh sieve to obtain a powder.
10. The method for manufacturing mullite-high silica glass composite material using hard clay according to claim 1, characterized in that: In step (3), the pressing pressure is 80 MPa, the drying temperature is 105-108° C., and the drying time is 24 h; and in step (4), the holding time is 3.3-3.5 h.
Citation Information
Patent Citations
Method and system for preparing mullite and high-silica glass composite refractory material
CN106431443A
Mullite-based plastic refractory and preparation method thereof
CN107216158A
Mullite micro-nano pore heat insulation refractory material and preparation method thereof
CN114133258A
Method for preparing mullite refractory material and mullite refractory material
CN116947512A
Synthetic compact aggregate of aluminium silicate and its preparing process
CN1249285A
Cited By
High-porosity mullite-high-silica glass composite thermal-insulation refractory material and preparation method thereof
CN122771753A